Increasing the capacity of natural killer (NK) cells in fighting advance stage ovarian cancer: A cellular immunotherapy minireview - Radiana Dhewayani Antarianto; Fransisca Dela Verna; Lady Feren Pangjaya; Sanya Khaerunnisa; Dinda Shezaria; Tricia Dewi Anggraeni (Institut Teknologi Bandung, 2020)
Global Cancer Statistics in 2018 estimated 300,000 new cases of ovarian cancer with 152,000 mortality rate each year. The Indonesian Society of Gynecologic Oncology reported 30% of gynecologic cancer is ovarian cancer, which has a 125, 000 mortality rate each year. Ovarian cancer data in Indonesia showed that 70% of patients were diagnosed with ascites or metastasis beyond the ovaries (stage III or IV). Ovarian cancer is an immunogenic disease with an immunotherapy intervention on the horizon. To assess the potency of stimulated NK cells as ovarian cancer cellular immunotherapy, literature search was collected from NCBI, ScienceDirect and Pubchem database. A total of 19 articles relevant to our search terms were included in this review. NK cells from ovarian cancer ascites exhibit low cytotoxic efficacy but can be restimulated using IL-2 or IL-15. An in vitro study that incubated NK cells with an IL-15 fusion protein enhanced the function of the ovarian cancer ascites’ NK cells or the healthy NK cells against the ovarian cancer ascites cells. Human IL-12-, IL-15- and IL-18-induced memory like (CIML) NK cells, has been proven to increase the elimination of xenograft human ovarian cancer cells over a long period of time in a mouse model. CIML NK cells also showed higher NK cell expansion and an enhanced function in the ovarian cancer ascites’ microenvironment, which was immunosuppressive. Phase I-II clinical trials on NK cell-based adoptive cellular therapies demonstrated limited clinical benefit. The major challenges are obtaining persistent NK cells with anticancer activity.